Analisa Tingkat Kepuasan Pengguna Elearning Menggunakan EUCS dan Model Delone and McLean - Indah Purwandani (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Elearning is now a necessity to support the implementation of learning in various educational institutions. End User Computing Satisfaction (EUCS) is a method used to measure the level of satisfaction of users of an application system by comparing expectations and reality of an information system. In this study 5 EUCS indicators were measured which would determine the level of Elearning user satisfaction, namely content, accuracy, shape, ease of use and timeliness. In the Delone And McLean Model there are six factors which are indicators, namely system quality, information quality, service quality, usage, user satisfaction, net benefits. Of the two methods will be measured how the level of elearning user satisfaction at Bina Sarana Informatics University. This study uses random samples collected through electronic questionnaires. There are several limitations in this study and further studies are needed so that the level of elearning user satisfaction can be described correctly. Keywords: elearning, eucs, endusercomputingsatisfaction, delonemclean